Links between Disease Severity, Bacterial Infections and Oxidative Stress in Cystic Fibrosis - Sabina Galiniak; Mateusz Mołoń; Marta Rachel (MDPI AG, 2022)
Cystic fibrosis (CF) is one of the most common, yet fatal genetic diseases in Caucasians. The presence of a defective CF transmembrane conductance regulator and the massive neutrophils influx into the airways contribute to an imbalance in epithelial cell processes and extracellular fluids and lead to excessive production of reactive oxygen species and intensification of oxidative stress. The study included 16 controls and 42 participants with CF aged 10 to 38. The products of protein oxidation, total antioxidant capacity (TAC) and markers of lipid peroxidation were estimated in the serum of the subjects. Furthermore, we compared the level of oxidative stress in patients with CF according to the severity of disease and type of bacterial infection. Thiol groups and serum TAC decreased significantly in patients with CF (p < 0.05). Elevated levels of 3-nitrotyrosine, malondialdehyde and 8-isoprostane were observed in CF subjects (p < 0.05). Furthermore, as the severity of the disease increased, there was a decrease in the thiol groups and TAC levels, as well as an increase in the concentration of 3-nitrotyrosine and 8-isoprostane. CF participants infected with Pseudomonas aeruginosa had elevated 3-nitrotyrosine concentration levels (p < 0.05), while those infected with Staphylococcus aureus noted a decrease in thiol groups (p < 0.05). Elevated levels of oxidative stress markers were found in the serum of CF patients. Furthermore, oxidative stress progressively increased over the years and along with the severity of the disease. The presence of bacterial infection with P. aeruginosa or S. aureus had a slight effect on oxidative stress, while co-infection by two species did not affect the level of oxidative stress.